2009
DOI: 10.1073/pnas.0811851106
|View full text |Cite
|
Sign up to set email alerts
|

Biodesign of a renal-protective peptide based on alternative splicing of B-type natriuretic peptide

Abstract: Alternative RNA splicing may provide unique opportunities to identify drug targets and therapeutics. We identified an alternative spliced transcript for B-type natriuretic peptide (BNP) resulting from intronic retention. This transcript is present in failing human hearts and is reduced following mechanical unloading. The intronretained transcript would generate a unique 34 amino acid (aa) carboxyl terminus while maintaining the remaining structure of native BNP. We generated antisera to this carboxyl terminus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…38 Indeed, human BNP activates cGMP generation in isolated canine glomeruli. 39 While our results suggest comparable actions between M-ANP and human BNP our conclusions need to be cautious due to differences in human and canine BNP.…”
Section: Discussionmentioning
confidence: 58%
“…38 Indeed, human BNP activates cGMP generation in isolated canine glomeruli. 39 While our results suggest comparable actions between M-ANP and human BNP our conclusions need to be cautious due to differences in human and canine BNP.…”
Section: Discussionmentioning
confidence: 58%
“…Another example of biodesigner peptide is alternatively spliced BNP (ASBNP). This peptide has also shown to retain renal effects while lacking vascular effects of BNP in a canine model of CHF [51]. Specifically, ASBNP did not alter mean arterial pressure and increased GFR; also, ASBNP suppressed plasma renin and angiotensin II while inducing natriuresis and diuresis compared with BNP.…”
Section: Biodesigner Peptidesmentioning
confidence: 95%
“…In vivo, intravenous administration of ANX-042 in a canine model of pacing-induced HF significantly enhanced diuresis, natriuresis, and GFR without reducing mean arterial pressure (65). Data from a Healthy Volunteer Dose Escalation Study (NCT01638104) furthermore showed that infusion with ANX-042 is safe and results in cGMP-activation (Table 1).…”
Section: Designer Nps: For CV Diseasementioning
confidence: 99%